A METHOD OF CONTROLLED N-DOPING OF GROUP III-V MATERIALS GROWN ON (111) SI - BUGGE, Renato; MYRVÅGNES, Geir (2022)
The present invention is related to a method of providing n-doped group III-V materials grown on (111) Si, and especially to a method comprising steps of growth of group III-V materials interleaved with steps of no growth, wherein both growth steps and no growth steps are subject to a constant uninterrupted arsenic flux concentration.